FAKTOR-FAKTOR INTERNAL YANG MEMPENGARUHI HASIL BELAJAR MATERI JURNAL PENYESUAIAN PADA SISWA KELAS XI IPS SMA NEGERI 2 NGAWI - Chomsiatun, Siti (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2013)
This study aims to determine the internal factors that influence the outcome of learning material of adjusting entries on grade XI of Social class in 2nd State Senior High of Ngawi. Population of this study was 124 students. Using a quota sampling technique, 92 students were selected as samples. Data were collected by using questionnaires, documentations and interviews. This study was using quantitative analysis with multiple linear regression. Based on the results of the t test, this study concluded that there is health effect on students learning outcomes, there is intelligence influence on students learning outcomes, there is influence of students interest towards learning outcomes, whereas no effect of fatigue on learning outcomes of students . Based on the F test concluded that the health, intelligence, interest and fatigue simultaneously significant effect on the improvement of learning outcomes. Based on the conclusion, further research is suggested to be doing research for the improvement of learning outcomes with respect to adjusting journal material variables that influence learning outcomes on student material adjusting entries in accordance with the findings of this study.